Aptidão cardiorrespiratória e atividade neuromuscular de pacientes recuperados da COVID-19 - Costa, Murillo Frazão de Lima e (2021)
Introduction: at the end of December 2019, a new coronavirus, called the severe acute respiratory syndrome corona virus 2 (SARS-CoV-2), was the cause of the 2019 corona virus disease pandemic (COVID-19). The disease affects multiple systems, presenting different physiological dysfunctions according to the degree of evolution. As a result of this multisystemic effect, it is reasonable to think that COVID-19 can decrease cardiorespiratory fitness and muscle performance. Objectives: to assess cardiorespiratory fitness and neuromuscular activity in patients recovered from COVID-19. We will also investigate the validity of electromyography (EMG) as a non-invasive method for detecting the anaerobic threshold and the respiratory compensation point in patients recovered from COVID-19. Methods: this is a crosssectional study. Patients recovered from COVID-19 mild to severe (less than 30 days) of both sexes were eligible, being compared with a control group of healthy individuals. Patients recovered from COVID-19 who required intubation and mechanical ventilation and those with previous cardiac, pulmonary, neurological, hematological or muscular diseases. The individuals were submitted to an evaluation by cardiopulmonary exercise test (CPET) associated with quadriceps EMG (vastus lateralis). From the CPET analysis, the following variables were considered: power, peak oxygen consumption (VO2), oxygen pulse at maximum effort (O2Pulse), cardiovascular efficiency (ΔHR / ΔVO2), peak ventilation (VE), respiratory reserve (BR ), ventilatory efficiency (VE / VCO2 slope), anaerobic threshold (LA) and respiratory compensation point (PCR). From the EMG analysis, root mean square (RMS), neuromuscular efficiency (Δwatts / Δ% RMS) and the first and second inflection points of the EMG were considered during the effort. Results: patients with severe COVID-19 had lower VO2, O2Pulse and LV than patients with mild COVID-19 and healthy individuals (p <0.05 for all comparisons). There were no differences in ΔHR / ΔVO2, BR or VE / VCO2 slope between groups (p> 0.05 for all comparisons). Type IIa and IIb fibers were activated at a lower potency in critically ill patients than in patients with mild COVID-19 and healthy individuals (p <0.05). Δwatts / Δ% RMS was lower in critically ill patients than in mild COVID-19 and healthy individuals (p <0.05). EMG and gas exchange analysis showed a strong correlation in the detection of the anaerobic threshold (r = 0.97, p <0.0001) and the respiratory compensation point (r = 0.99, p <0.0001). The Bland-Altman analysis showed a bias of -4.7 watts for LA detection in EMG compared to the gas exchange analysis and a bias of -2.1 watts in the detection of PCR. Conclusion: patients recovered from severe COVID-19 have less cardiorespiratory fitness and neuromuscular efficiency (a fact not observed in patients recovered from mild COVID-19) and EMG can be used as a non-invasive method for detecting LA and CRP in these patients.